2008
DOI: 10.1097/mlg.0b013e31815659b0
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Swallowing Exercises Improve Swallow Function After Chemoradiation

Abstract: Performing pretreatment swallowing exercises produces measurable improvements in posttreatment swallowing function in patients who undergo organ-preservation CRT for head and neck cancer. This study provides an initial foundation for the development of noninvasive, cost-effective, evidence-based interventions in this group of vulnerable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
163
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(170 citation statements)
references
References 34 publications
1
163
3
3
Order By: Relevance
“…After the designated period of this systematic search had ended, several additional papers were published, three of which (Carroll et al [97], Logemann et al [103] and Langerman et al [104]) warrant a brief review. Carroll et al and Logemann et al suggested that (early) rehabilitation might be beneWcial.…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…After the designated period of this systematic search had ended, several additional papers were published, three of which (Carroll et al [97], Logemann et al [103] and Langerman et al [104]) warrant a brief review. Carroll et al and Logemann et al suggested that (early) rehabilitation might be beneWcial.…”
Section: Generalmentioning
confidence: 99%
“…Many tongue and swallowing exercises, such as tongue function therapy and swallowing maneuvres, are described in the literature [17,21,48,[97][98][99][100][101][102]. Furthermore, the eVectiveness of these swallowing exercises has not yet been assessed systematically in the CRT patient population.…”
Section: Generalmentioning
confidence: 99%
“…This method was pioneered by Ogilvie et al [50] and more recently utilised by Crowther et al [51] to provide a visual display of synthesised evidence, where lack of homogeneity between studies has precluded the traditional use of a forest plot. The average TREND score was 13.8 (range, [10][11][12][13][14][15][16][17][18]. Despite the variable scorings, studies were deemed to have sufficiently comparable quality in their methodology and reported findings, hence none warranted exclusion from the final cohort.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Historically, treatment approaches have been reactive, with rehabilitation administered after medical intervention (either surgical or non-surgical). However, emerging evidence [15][16][17][18][19] has instigated a shift towards the use of preventative dysphagia rehabilitation, based on the premise that proactively exercising swallowing structures known to be negatively impacted by radiation may limit the extent of (C)RT-induced dysfunction [20].…”
Section: Introductionmentioning
confidence: 99%
“…24 Pretreatment swallowing exercises produces measurable improvements in post-treatment swallowing function in patients who undergo organ-preservation chemoradiation (CT/RT) for head and neck cancer and might reduce dependence on PEG. 25 With rising interest in organ preservation, more and more radical radiotherapy and intensive multimodal treatment would be pursued. Whilst deciding the need for tube enterostomies in patients for radiotherapy alone consideration should be given to absolute dose, volume, time-frame and whether brachytherapy is added or not.…”
Section: Head and Neck Cancer-clinical Considerationsmentioning
confidence: 99%